Algorithm for Making Administrative Decisions in Supply Chain Management at the Stages of â€œLife Cycleâ€ of Enterprise - N.G Antonchenko; V.A Saydasheva (International Journal of Supply Chain Management, 2019)
The present article defines the possibility of optimizing key managerial solutions in business organization based on an improved algorithm of actions that takes into account the stage of â€œlife cycleâ€ of enterprise. The tactics of phased implementation of management decisions at each stage of â€œlife cycleâ€ of the business structure has been clarified and substantiated. This has allowed to reduce the number of out-of-plan adjustments, to break the subsequent implementation of optimized actions short, and to determine the forecast effectiveness of managerial actions based on statistical analysis. The list of indicators that characterize the managerial aspect of the progressive development of the entrepreneurial structure has been systematized. The results of the analysis of data from regional business structures at different stages of â€œlife cycleâ€ confirm the correctness of the choice of indicators. Both marketing and logistical aspects which make it possible in the end to choose the most profitable option of commercial action organically complement the algorithm of managerial decision-making proposed by the authors. In general, this analytical approach to taking into account the dependence of the cumulative effect on the set and mutual influence of factors will provide the flexibility of business organization and shorten the period of achievement of strategic goals.